Structure and Properties of Nanosize NiFe2O4 Prepared by Template and Precipitation Methods (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Nanosize NiFe2O4 was prepared by template method and precipitation process using same starting materials. The use of soluble starch in both synthesis routes was investigated. The amount of the used precipitating agent (Na2CO3) for the precipitation approach was selected according to two adopted scenarios based on theoretical and average yield of possible side reaction expressed by the degree of substitution (DS). The results of SEM microstructural analysis of the prepared Ni-ferrite powders demonstrate evident influence of the applied preparation method whereas high-magnification FE-SEM images show very similar fine-grained structures characterized by different size of particles. According to the results of XRD analysis, the obtained ferrite powders exhibit only slight differences in phase composition with calculated crystallite size for template sample dXRD = 36 nm and for the both precipitation route samples dXRD = 21 nm. Additional sample characterization using 57Fe Mössbauer spectroscopy supports the findings of the microstructural and XRD analysis. The “clearest” spectrum was obtained for the template sample while the strongest influence of nanocrystalline component was observed for the sample prepared with maximal amount of precipitation agent (DS=3). The room temperature magnetic hysteresis loops, recorded using vibrating sample magnetometer (VSM), are very similar and exhibit characteristic shape with values of magnetic properties within expected range for this type of material.
Keywords: phase composition; microstructures; Precipitation; nanocrystalline materials; magnetic properties